THE EFFECT OF AGE, EDUCATIONAL ATTAINMENT, AND NUMBER OF DEPENDENTS ON THE INCOME OF FEMALE TRADERS AT GALIRAN MARKET, KLUNGKUNG - Putu Intan Elvina Karunia Wisnuadi; Ni Luh Karmini (CV. Adiba Aisha Amira, 2025)
This study aims to analyze the effect of age, educational attainment, and number of dependents on the income of female traders at Galiran Market, Klungkung, both simultaneously and partially. The research employs a quantitative method with an associative approach. The population consists of all female traders at Galiran Market, totaling 1,039 individuals, with a sample of 92 respondents determined using the Slovin formula and purposive sampling technique. The data were analyzed using multiple linear regression, accompanied by classical assumption tests to ensure the model’s validity. The findings reveal that age, educational attainment, and number of dependents simultaneously have a significant effect on the income of female traders at Galiran Market. Partially, age and educational attainment have a positive and significant effect on income, while the number of dependents does not have a significant effect.